ON MAXIMAL CHAINS IN POSETS WITH GROUP ACTIONS - Abdul Aali J. Mohammad; Abbas Kathim (College of Education for Pure Sciences, 2007)
ABSTRACT Our main purpose in this work is to study the maximal chains in group-posets to observe that this study gives us indications on the type of some group actions on posets. Therefore we shall study the behavior of the group actions on chains .